The impact of emotional development in people with autism spectrum disorder and intellectual developmental disability. Issue 12 (12th October 2020) - Sappok, T.; Heinrich, M.; Böhm, J.
Abstract: Background: Intellectual developmental disabilities (IDDs) and autism spectrum disorders (ASDs) are developmental conditions, which may also be associated with impairments in emotional development (ED). ED can be assessed using the Scale of Emotional Development – Short (SED‐S), a five‐stage model consisting of eight domains, which allows to study the relationship between ASD and ED in people with IDD. Methods: In this retrospective study, the level of ED was compared in 327 adults with IDD with [ n = 83; mean age 38.3 years; level of IDD: mild (6), moderate (21), severe (45) and profound (11)] and without [ n = 244, mean age 36.9 years; level of IDD: mild (67), moderate (73), severe (68) and profound (36)] ASD. The discriminative ability of the SED‐S was determined by a regression in a training and a validation sample. Results: The level of ED correlated with the severity of IDD ( r s = −.654) and the presence of ASD ( r s = −.316). People with additional ASD showed lower levels of ED compared with those with IDD only (mean reference ages 7–18 vs 19–36 months). The developmental profiles were equally balanced in ASD and IDD‐only. A regression analysis revealed three domains ('Relating‐to‐Peers', 'Differentiating‐Emotions', and 'Regulating‐Affect') to be useful for ASD assignment (AUC > 0.70, sensitivity 0.76–0.80, specificity 0.62–0.63). Conclusions: In people with IDD, additional ASD was associated with delays in ED, which may be considered in diagnostics, treatment and care.